Almammadova, Sabina - (:unkn) unknown (My University, 2026)
Sabina Almammadova was born on 18 March 1972 in Baku. From 1989 to 1994, she studied at Azerbaijan University of Languages, Faculty of English Language. Between 1994 and 2004, she worked as a Leading Specialist in the Department of Analytical Information at Azerbaijan National Academy of Sciences, and also served as Executive Secretary and translator of the journal *Azerbaijan and Azerbaijanis*. Since 2003, she has been employed as a Senior Researcher in the Department of History of the Soviet Period of Azerbaijan at the A.A. Bakikhanov Institute of History. Since 2008, she has been teaching English at the Department of Foreign Languages of Azerbaijan Technical University. In the same year, she defended her PhD dissertation at the Institute of Linguistics named after I. Nasimi on the topic *The Language of Bakhtiyar Vahabzadeh’s Poetry*. In 2010, by decision of the Higher Attestation Commission under the President of the Republic of Azerbaijan, she was awarded the academic title of Associate Professor in the field of Foreign Languages. From 2016 to 2018, she served as the Lead Coordinator of the project *Borrowings in the Vocabulary of the Azerbaijani Language*. In 2018, she defended her doctoral dissertation at the Institute of Linguistics named after I. Nasimi for the degree of Doctor of Philology on the topic *Forms of Unification and Standardization of Borrowed Terms in the Modern Azerbaijani Literary Language*. She translated 25 books published by the A.A. Bakikhanov Institute of History into English, which were subsequently published in New York, London, Bishkek, and other locations. She is the author of 3 teaching manuals, 4 dictionaries, 6 monographs, and 97 scholarly articles published in Azerbaijan and abroad, including in the United States, Australia, India, Canada, Turkey, Georgia, Russia, and Ukraine. Sabina Almammadova has participated in numerous international and national conferences. She is also a member of the Expert Council of the Humanities Division of the Higher Attestation Commission. Since 17 August 2020, she has been serving as Acting Head of the Department of Foreign Languages at Azerbaijan Technical University.